Removal of Lead (II) Ions from Aqueous Solutions onto Activated Carbon Derived from Waste Biomass - Murat Erdem; Suat Ucar; Selhan Karagöz; Turgay Tay (The Scientific World Journal)
The removal of lead (II) ions from aqueous solutions was carried out using an activated carbon prepared from a waste biomass. The effects of various parameters such as pH, contact time, initial concentration of lead (II) ions, and temperature on the adsorption process were investigated. Energy Dispersive X-Ray Spectroscopy (EDS) analysis after adsorption reveals the accumulation of lead (II) ions onto activated carbon. The Langmuir and Freundlich isotherm models were applied to analyze equilibrium data. The maximum monolayer adsorption capacity of activated carbon was found to be 476.2 mg g−1. The kinetic data were evaluated and the pseudo-second-order equation provided the best correlation. Thermodynamic parameters suggest that the adsorption process is endothermic and spontaneous.